Problema Integrasi-Interkoneksi Pendidikan Agama Islam dalam Upaya Penguatan Kebijakan Inovasi Merdeka Belajar di Pesisir Selatan - Pasaleron, Roni; Nurdin, Syafruddin; Kosim, Muhammad (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2022)
The most basic internal problem is the teaching staff (teachers) of BAM and al-Qur'an education in designing and compiling teaching materials, in determining the way of presentation, in determining the direction of learning, and in outlining learning objectives. With that creativity, learning will be efficient and effective. While the external problem is the problem of implementing BAM learning outcomes in the Minangkabau community. Qualitative research with the type of field research and descriptive methods. Collecting data by observation, interviews and documentation. Efforts are needed to integrate and interconnect Islamic religious education in order to strengthen the innovation policy for independent learning in the Pesisir Selatan. Efforts that must be made in order to create a PAI integration-interconnection program in the context of Strengthening the Free Learning Innovation merdeka belajar by the Dinas Pendidikan Kabupaten Pesisir Selatan and Kementerian Pendidikan Agama Pesisir Selatan can achieve their goals. The implementation method can be carried out in two stages, including through seminars and workshops/mentoring for making lesson plans, media and PAI teaching materials that are integrated-interconnected with Al-Qur'an Education and Minangkabau Natural Culture.